A Multi-Scale Modelling Approach and Experimental Calibration Applied to Commercial SOFCs. (30th May 2017) - Mastropasqua, Luca; Donazzi, Alessandro; Campanari, Stefano
Abstract : The present study aims at laying the theoretical basis for a multi-scale modelling approach applicable to state-of-the-art commercial SOFCs. The proposed multi-scale model is built with the main purpose to understand how micro-scale characteristics of the PEN structure and the thermo-chemical and electrochemical phenomena, which occur in the electrode and electrolyte assembly, may affect the overall performance of a complete cell and ultimately of the stack. This study presents the integration of two-dimensional finite volume models: a 1D micro-scale model and a 1D (or 2D) macro-scale (channel/cell) model. The analysis evidences how stack optimisation should focus on the micro-structure characteristics, which should also change along the reactant channels ( x direction) in relation to the local variation of temperature and composition. The model therefore lays the basis for cell local optimisation and design-led techniques required for performance enhancement.